The relationship between monetary rewards and job satisfaction among administrative personnel at selected public schools in Maran district, Pahang / Nurfarina Amran - Amran, Nurfarina (Faculty of Business and Management, 2019)
This research paper was aimed to investigate the correlations between monetary rewards and job satisfaction among administrative personnel in selected public schools at Maran District. Pahang. 50 respondents completed the survey questionnaire which was adopted from Minnesota Satisfaction Questionnaire (1967) and Robles (2018). This study used all population as the respondent and the response rate was 100%. SPSS V-20 was used to analyze the questionnaires in order to determine the result. Most of the respondents were from Sekolah Menengah Kebangsaan Jengka Pusat 2, with grade position of N19. The respondents have a salary range of RM2,001 - RM3,000 and have 10 to 15 years working experience. The findings showed that there was strong relationship between monetary rewards and job satisfaction among administrative personnel at selected public school in Maran District, Pahang (r=0.70, p=0.00). However, there is no correlation between salary and job satisfaction (r=0.07, p=0.60) and the finding indicates the correlation was insignificant for bonuses and job satisfaction (r=0.26, p=0.07) as well. The findings also shows that the correlation was significant as a result between allowance and job satisfaction (r=0.87, p=0.00). Generally, administrative personnel's satisfaction was highly satisfied were (M=3.70, SD=0.78). It is recommended that the organization should improve workers skills, consistently give praise and improve working condition as well as work environment. Future study should increase sample size and focus not only public schools but private schools as well. Future researcher should investigate other types of employees that serve in schools environment including teachers.